Thermoelectrical Effect in SiC for High-Temperature MEMS Sensors - Dinh, Toan.; Nguyen, Nam-Trung.; Dao, Dzung Viet.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2018)
This book presents the fundamentals of the thermoelectrical effect in silicon carbide (SiC), including the thermoresistive, thermoelectric, thermocapacitive and thermoelectronic effects. It summarizes the growth of SiC, its properties and fabrication processes for SiC devices and introduces the thermoelectrical sensing theories in different SiC morphologies and polytypes. Further, it reviews the recent advances in the characterization of the thermoelectrical effect in SiC at high temperatures. Discussing several desirable features of thermoelectrical SiC sensors and recent developments in these sensors, the book provides useful guidance on developing high sensitivity and linearity, fast-response SiC sensing devices based on thermoelectrical effects.
Introduction to SiC and Thermoelectrical Properties -- Fundamentals of Thermoelectrical Effect in SiC -- Desirable Features for High Temperature SiC Sensors -- Fabrication of SiC MEMS Sensors -- Impact of Design and Process on Performance of SiC Thermal Devices -- Applications of Thermoelectrical Effect in SiC -- Future prospects of SiC Thermoelectrical Sensing Devices.
Keywords: Nanotechnology; Microtechnology; Microelectromechanical systems; Condensed matter; Nanotechnology; Microsystems and MEMS; Condensed Matter Physics